The Role of IFRS 7 in Shaping Investor Behavior: The Moderating Effect of Value Relevance in Iraqi Stock Exchange (ISX) - Rasheed, Hasanain Salim (CV. Proaksara Global Transeduka, 2025)
The study aims to explore the effect of financial disclosure under IFRS 7 on investor behavior in Iraqi stock exchange, with focusing on role of value relevance as a moderating variable. The study population was represented by Investors’ and Iraqi banking sector in ISX, while a sample of 10 banks was selected based on the ease of accessibility, continuity of their banking operations and their cooperation in providing the required data. The Smart PLS was used to analysis data. Moreover, the study was conducted retrospectively (ex- post factor), and for testing the structural model through bootstrapping analysis with 500 subsamples. The results of the study showed that market risk disclosure is important and plays a major role in investor’s decisions compared to other disclosures. In addition, liquidity risk disclosure came second after market risks, reflecting the ability of banks to meet their short-term obligations. Finally, credit risk disclosure was less influential than other disclosures, suggesting that investors in the Iraqi Stock Exchange are more sensitive to market and liquidity risks. As our results showed, banks should improve disclosure and compliance with IFRS 7 requirements in order to avoid any frailer in future. In addition, regulators and banks should work to simplify financial reports and increase their clarity for investors in the ISX.